2017
DOI: 10.1038/s41598-017-14883-y
|View full text |Cite
|
Sign up to set email alerts
|

Universal glass-forming behavior of in vitro and living cytoplasm

Abstract: Physiological processes in cells are performed efficiently without getting jammed although cytoplasm is highly crowded with various macromolecules. Elucidating the physical machinery is challenging because the interior of a cell is so complex and driven far from equilibrium by metabolic activities. Here, we studied the mechanics of in vitro and living cytoplasm using the particle-tracking and manipulation technique. The molecular crowding effect on cytoplasmic mechanics was selectively studied by preparing sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
105
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 77 publications
15
105
0
Order By: Relevance
“…We introduce a model of bacterial cytoplasm focusing on the effect of non-SPP-type activity, in which proteins are modeled as particles under thermal agitation and their conformational change is taken into account as a change in the volume of the particles. By means of a molecular dynamics (MD) simulation of the model, we show that small changes in particle volume drastically accelerate the dynamics and alter the fragility from fragile to strong, as observed in previous experiments [19].…”
supporting
confidence: 75%
“…We introduce a model of bacterial cytoplasm focusing on the effect of non-SPP-type activity, in which proteins are modeled as particles under thermal agitation and their conformational change is taken into account as a change in the volume of the particles. By means of a molecular dynamics (MD) simulation of the model, we show that small changes in particle volume drastically accelerate the dynamics and alter the fragility from fragile to strong, as observed in previous experiments [19].…”
supporting
confidence: 75%
“…The transient GAPDH-LDH complex that forms in experiments with purified enzymes can be much more durable in concentrated protein solution in cytosol or in cell extracts 14,15,46 . The high protein concentrations can produce excluded volume effects that can increase the interaction energy (Δ G ) by favoring protein-protein interactions that can decrease the number of water molecules trapped in hydration shells 14,15,46 . It is also necessary to notice that in cytosol LDH-GAPDH complex can be a part of much larger glycolytic metabolon 8-10 .…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the concentration of intracellular macromolecules is called "macromolecular crowding". In freezing studies on bacterial cytoplasm, glass-like properties have been reported to differ from those outside the cell [49,50]. In Lactobacillus and several other organisms, it has been described that osmotic dehydration emphasizes the intracellular macromolecular crowding.…”
Section: Intracellular Crowding and The Colloidal Vitrificationmentioning
confidence: 99%